2022
DOI: 10.3390/cancers14133088
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Stromal Cell Regeneration Profile in Treated B-Cell Precursor Acute Lymphoblastic Leukemia Patients: Association with MRD Status and Patient Outcome

Abstract: For the last two decades, measurable residual disease (MRD) has become one of the most powerful independent prognostic factors in B-cell precursor acute lymphoblastic leukemia (BCP-ALL). However, the effect of therapy on the bone marrow (BM) microenvironment and its potential relationship with the MRD status and disease free survival (DFS) still remain to be investigated. Here we analyzed the distribution of mesenchymal stem cells (MSC) and endothelial cells (EC) in the BM of treated BCP-ALL patients, and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Both populations of BM‐derived stromal cells might thereby be used as a measure of sample quality and hemodilution, as they are virtually undetectable in blood at the 10 −5 to 10 −6 levels. Recent studies have shown that these cells are associated with patient outcome and can be used as a prognostic marker in BCP‐ALL patients (Fallati et al, 2022; Oliveira et al, 2022). CD10+ MSCs and CD34+ ECs are generally not identified in manual analysis, and the lack of experience with such cells may explain the overall lower concordance between manual and AGI supported analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Both populations of BM‐derived stromal cells might thereby be used as a measure of sample quality and hemodilution, as they are virtually undetectable in blood at the 10 −5 to 10 −6 levels. Recent studies have shown that these cells are associated with patient outcome and can be used as a prognostic marker in BCP‐ALL patients (Fallati et al, 2022; Oliveira et al, 2022). CD10+ MSCs and CD34+ ECs are generally not identified in manual analysis, and the lack of experience with such cells may explain the overall lower concordance between manual and AGI supported analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence suggests that acute myelogenous leukemia (AML)-associated BM-MSCs show reduced CXCL12 and SCF expression with reduced sinusoidal and increased arterial cell populations ( Arranz et al, 2014 ; Baryawno et al, 2019 ). Furthermore, an imbalanced BM-MSC/endothelial cell ratio in B-cell precursor acute lymphoblastic leukemia (BCP-ALL) post-therapy associated with a shorter disease-free survival, irrespective of minimal residual disease status ( Oliveira et al, 2022 ). Likewise, myelodysplastic syndrome (MDS)-driving mutations require the presence of altered stromal cells and MSCs in an aged milieu, where they express senescence markers, elevated inflammatory molecules, and reduced levels of cytokines required for normal hematopoiesis ( Huang et al, 2015 ; Fernando et al, 2019 ; Plakhova et al, 2023 ).…”
Section: Role Of Mscs and Their Adipocytic Lineage In Hematological M...mentioning
confidence: 99%
“…Accurate classification, appropriate treatment assignment, and constant monitoring have been shown to enhance the effectiveness of treatment in patients with childhood leukemia from different parts of the world, particularly in developed countries, where resources are sufficient. It is well known that the detection of MRD is the most significant predictor of unfavorable outcomes in patients with AL (17)(18)(19)(20)(21)(22)(23)(24); however, there are other factors, such as molecular abnormalities, which are also important prognostic factors in AL. Moreover, an early diagnosis and timely initiation of treatment in children with acute leukemia translate to higher survival rates.…”
Section: Introductionmentioning
confidence: 99%